Pengaruh Deskripsi Jabatan (Job Description) dan Beban Kerja terhadap Kepuasan Kerja Karyawan Kontrak Bulanan (Studi pada PT Multi Garmenjaya) - Alifia Putri Widanti; Salma Nurpita Utami; Yusi Yuferina; Recky Recky (CV. ALIM'SPUBLISHING, 2026)
The purpose of this study is to identify the level of influence of job description and workload on the job satisfaction of monthly contract employees at PT Multi Garmenjaya. Through a cross-sectional survey method, this study applies a descriptive and associative research design. The data collection was carried out through the distribution of a combination of online (Google Form) and offline (print questionnaire) questionnaires to 87 respondents who were selected as a sample of the entire population totaling 677 monthly contract employees. Based on the results of hypothesis testing, it was found that the position description variable had a positive and partially significant influence on employee job satisfaction, with a calculated t-value of 5.529 and a significance level of 0.0000. On the other hand, the workload variable was also found to show a positive and significant influence on employee job satisfaction partially, with a calculated t value of 1.327 and a significance value of 0.188. When tested simultaneously, the two independent variables were proven to have a significant effect on the job satisfaction of contract employees, with an F score of 27.772 and a significance value of 0.0000. As for the Adjusted R Square value, a value of 0.384 was obtained. This figure means that the ability of the variable job description and workload in explaining the ups and downs of the job satisfaction of PT Multi Garmenjaya's monthly contract employees is 38.4%. Meanwhile, the other percentage, which is 61.6%, is influenced by other factors or variables that are not studied and studied in this research model.